Factors Affecting Systematic Implementation of Reduce and Recycle in Construction Industry - Mohd Nasrun Mohd Nawi; Wan Nadzri Osman; Rohaizah Saad; Radzi Ismail (International Journal of Supply Chain Management, 2017)
Most of the stakeholders involved in the construction industry, particularly from developing countries have less emphasis on environmental care primarily involves the reuse and recycle of building materials in their construction projects. Previous studies prove environmental aspects have been neglected by the major stakeholders of the construction industry compared with issues related to cost and time. This study focuses on identifying the current adoption level of reuse and recycle practice among Malaysian contractors, the factors that are required for the successful implementation of systematic reuse and recycle and to identify the relationship between the selected factors and systematic implementation of reuse and recycle. The questionnaires were distributed to class A contractors that registered with the Contractor Service Centre (PKK). Currently, most of the contractors are concerned about reuse and recycle of the construction materials.